(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Digital image forgery detection has become increasingly important due to the proliferation ofimage editing software and the rise in image-based social media platforms. Content-preserving forgeriespose a significant challenge to existing forgery detection techniques since they aim to maintain thevisual appearance of an image while introducing subtle alterations. This research paper proposes anovel method for detecting content-preserving image forgeries using Support Vector Machines (SVM),Convolutional Neural Networks (CNN), and ensemble classifiers of the machine learning algorithm.